Combating nurse burnout - Ho, Sweet Lee *; Nitiakaliyani, Balasubramaniam *; Sri Ameera, Abdul Rahim * (MalaysiaKini, 2023)
LETTER | Burnout among Malaysian nurses has reached alarming levels, as underscored by recent studies.